Agentic Engagement in Education: A Systematic Review of its Characteristics, Factors, and Impacts (2011–2024) - Utami, Rany Aprilia; Kurniawati, Farida (KONSELOR, 2024)
This systematic literature review examines the concept of agentic engagement, a form of proactive student involvement in learning defined by self-directed behaviours such as expressing preferences, seeking clarifications, and actively shaping the instructional environment. Previous research on engagement has predominantly focused on behavioural, emotional, and cognitive dimensions, making agentic engagement—which was introduced in 2011—a novel branch in the study of student engagement. Consequently, this review analyses studies published between 2011 and 2024, sourced from five major databases: Sage Journals, ScienceDirect, Scopus, SpringerLink, and Taylor & Francis. We identified and thoroughly reviewed a total of 15 eligible articles across three key dimensions: (1) characteristics of students exhibiting agentic engagement, (2) factors contributing to the development of agentic engagement, and (3) the impacts of agentic engagement on students' learning. Additionally, an in-depth analysis addresses ways to enhance agentic engagement through an intervention called the Autonomy-Supportive Intervention Program (ASIP). This analysis suggests that agentic engagement is a vital educational aspect, benefiting students by fostering academic resilience, self-efficacy, motivation, and school adjustment, while also reducing test anxiety. Teachers can cultivate supportive learning environments that foster student agentic engagement with the help of ASIP. The implications of agentic engagement extend beyond traditional classroom settings, providing valuable insights into student-centred practices that encourage self-determination and active participation. Furthermore, understanding agentic engagement can guide teachers in gaining deeper insights into their students and help them identify those who require greater encouragement or motivation. Additionally, counsellors can design targeted interventions to enhance agentic engagement in learning. This literature review highlights the transformative potential of agentic engagement in education, especially in school settings, and suggests promising avenues for future research.